2018
DOI: 10.5194/acp-18-5089-2018
|View full text |Cite
|
Sign up to set email alerts
|

A climatology of polar stratospheric cloud composition between 2002 and 2012 based on MIPAS/Envisat observations

Abstract: Abstract. The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument aboard the European Space Agency (ESA) Envisat satellite operated from July 2002 to April 2012. The infrared limb emission measurements provide a unique dataset of day and night observations of polar stratospheric clouds (PSCs) up to both poles. A recent classification method for PSC types in infrared (IR) limb spectra using spectral measurements in different atmospheric window regions has been applied to the complete mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(99 citation statements)
references
References 85 publications
11
88
0
Order By: Relevance
“…During the Arctic winter 2010/2011, the overall PSC occurrence frequency and area were exceptional for an Arctic winter as was shown by Manney et al (2011) and confirmed in a recent study by Spang et al (2018). The peak values of PSC area (in square kilometres) reached sizes comparable to June conditions in the Antarctic.…”
Section: Arctic Winter 2009/2010supporting
confidence: 73%
“…During the Arctic winter 2010/2011, the overall PSC occurrence frequency and area were exceptional for an Arctic winter as was shown by Manney et al (2011) and confirmed in a recent study by Spang et al (2018). The peak values of PSC area (in square kilometres) reached sizes comparable to June conditions in the Antarctic.…”
Section: Arctic Winter 2009/2010supporting
confidence: 73%
“…CALIPSO flies in a 98 • inclination orbit at an altitude of 705 km as part of the NASA A-train satellite constellation (Stephens et al, 2002), along with the Aqua, Aura, CloudSat, and Orbiting Carbon Observatory 2 (OCO-2) satellites. Although PSC studies are not a primary mission objective, CALIPSO is an ideal platform for studying polar processes, collecting data along 14-15 orbits per day with coverage from 82 • S to 82 • N latitude on each orbit.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, NAT and ice particle surface areas are calculated 10 within the CLaMS sedimentation module and now also transfered to and used within the chemistry module. First applications are shown in a paper by Grooß et al (2018).…”
Section: Sedimentation Modulementioning
confidence: 99%
“…Spang et al (2016) introduced 25 the methodology of the Bayesian Classifier (v1.2.8) for PSC cloud types. The classification method has been applied to the complete MIPAS data set (Spang et al, 2018).…”
Section: Mipasmentioning
confidence: 99%